Respon Pertumbuhan dan Produksi Tiga Varietas Selada pada Hidroponik Sistem Floating Raft - Carmia Dwi Pratiwi; Ari Susatyo Nugroho; Muhammad Anas Dzakiy (Balitbangda Provinsi Lampung, 2018)
This study aims to determine the growth response and production of three varieties of lettuce with hydroponic techniques using Floating Raft system terms of plant height, number of leaves and wet weight near input, middle and near output. Research time at May 19 - June 13 2018 at PT. Hydroponics Agrofarm Bandungan. Sampling was done by simple random sampling in all three varieties of lettuce is Jonction varieties L. sativa capitata, Romaine varieties L. sativa longifolia and Red Saladbowl varieties L.sativa crispa. Research using Completely Randomized Design with 3 replications. Data were analyzed using variance test (ANOVA) and continued using the 5% BNT test. The results showed that the highest growth response and production of three varieties of lettuce on the Floating Raft system hydroponic occurred in lettuce placed near the nutrition input.